2022
DOI: 10.3389/fmicb.2022.1027271
|View full text |Cite
|
Sign up to set email alerts
|

Investigating SARS-CoV-2 breakthrough infections per variant and vaccine type

Abstract: Breakthrough SARS-CoV-2 infections have been reported in fully vaccinated individuals, in spite of the high efficacy of the currently available vaccines, proven in trials and real-world studies. Several variants of concern (VOC) have been proffered to be associated with breakthrough infections following immunization. In this study, we investigated 378 breakthrough infections recorded between January and July 2021 and compared the distribution of SARS-CoV-2 genotypes identified in 225 fully vaccinated individua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…Other studies carried out by Blanquart et al and Dingemans et al have reported the same observation. 4 , 13 Moreover, consistent with the literature, 1 , 6 , 11 we found that infection in both complete and booster vaccinated individuals was characterized by faster clearance time than unvaccinated participants. This accelerated clearance time in vaccine recipients might potentially lead to reduced shedding of the virus and declined duration of infection.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Other studies carried out by Blanquart et al and Dingemans et al have reported the same observation. 4 , 13 Moreover, consistent with the literature, 1 , 6 , 11 we found that infection in both complete and booster vaccinated individuals was characterized by faster clearance time than unvaccinated participants. This accelerated clearance time in vaccine recipients might potentially lead to reduced shedding of the virus and declined duration of infection.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our findings, while Dingemans et al reported a higher proportion of breakthrough infection in individuals vaccinated with the adenoviral-based vaccines compared to the mRNA-based vaccines, they observed no significant difference when the type of the vaccine used and the RNA load were compared. 4 …”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D sufficiency would reduce the incidence and severity of chronic diseases, such as metabolic disorders (e.g., diabetes, obesity, insulin resistance), cancer, autoimmune disorders, and infections [ 155 , 156 , 157 , 158 ]. While the efficacy of vaccines is wading with emerging new mutant Omicron viruses [ 159 , 160 ] and breakthrough SARS-CoV-2 infections [ 161 ], the effectiveness of vitamin D will not be affected [ 55 ]. Community vitamin D sufficiency is the key to protecting vulnerable populations, especially older people and ethnic minorities with darker skin color, and institutionalized persons [ 41 , 122 , 136 , 162 ].…”
Section: Discussionmentioning
confidence: 99%
“…Viral load was determined via RT-PCR analysis as previously described ( Dingemans et al, 2022 ). Only samples that were tested using the same laboratory workflow were included to compare the viral load in this study.…”
Section: Methodsmentioning
confidence: 99%